Analisis Perbandingan Gramatikal-Historis Bahasa Lidah dalam 1 Korintus dan Kisah Para Rasul - Yohanes Hasiholan Tampubolon; Aeron Frior Sihombing; Geri Gehotman Mangasake; Hafa’ akhododo; Maria Mayda Bunge Tana; Ricky Pianto Randa; Williams Jefferson Bill Walimena (Sekolah Tinggi Teologi Berita Hidup, 2021)
Glossolalia is currently a relevant topic. There is much controversy and debate about the practice of speaking in tongues. This paper will conduct a comparative analysis of tongues in 1 Corinthians and Acts. The practice referred to is specifically whether the Bible allows simultaneous speaking in tongues based on both books. Also regarding the speaking in tongues, whether it must be understood by others or is it necessary for someone to interpret it. This situation also occurs in the current context. Believers in some churches when in a worship (singing or praying) together speaking in tongues and without interpretation. The author finds that there are significant differences regarding the practice of speaking in tongues as instructed by Paul in 1 Corinthians and the story of speaking in tongues as written by Luke in Acts. In fact, there is an interpretive vacuum that contemporary interpreters must fill. The author uses a comparative method and a grammatical-historical hermeneutic approach to the biblical text.